2016
DOI: 10.1111/apa.13458
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and characteristics of suicide attempts among 381 suicidal adolescents

Abstract: Early risk factors for suicide were dissociated relationships with parents, siblings and friends, feeling unheard, self-mutilation and extended suicidal ideation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 31 publications
3
22
0
8
Order By: Relevance
“…5 In adolescence, certain particularities proper to this age increase risk of intentional self-harm, such as (i) profound biopsychosocial transformations, (ii) behavior that is naturally more impulsive and depressive, (iii) increased mental disorders, (iv) greater susceptibility to alcohol and drug consumption, (v) loneliness, (vi) questioning about social problems, meaning of life and belonging to the world, (vii) increased family conflicts, mostly arising from the quest for autonomy, (viii) crises or break-ups with boy/girlfriends or friends and (ix) temerity in social and sexual contacts. 3,[6][7][8][9] All of this context of vulnerability places intentional self-harm as a serious Public Health problem, and adolescence as a period of life when this problem is a leading cause of death. 3,10 In 2012, suicide was in third place among causes of adolescent deaths worldwide, after traffic accidents and respiratory infections.…”
Section: Introductionmentioning
confidence: 99%
“…5 In adolescence, certain particularities proper to this age increase risk of intentional self-harm, such as (i) profound biopsychosocial transformations, (ii) behavior that is naturally more impulsive and depressive, (iii) increased mental disorders, (iv) greater susceptibility to alcohol and drug consumption, (v) loneliness, (vi) questioning about social problems, meaning of life and belonging to the world, (vii) increased family conflicts, mostly arising from the quest for autonomy, (viii) crises or break-ups with boy/girlfriends or friends and (ix) temerity in social and sexual contacts. 3,[6][7][8][9] All of this context of vulnerability places intentional self-harm as a serious Public Health problem, and adolescence as a period of life when this problem is a leading cause of death. 3,10 In 2012, suicide was in third place among causes of adolescent deaths worldwide, after traffic accidents and respiratory infections.…”
Section: Introductionmentioning
confidence: 99%
“…Research carried out in Denmark in 2016 disclosed that children, in comparison with adults, more often try to commit suicide spontaneously. This finding was explained by the fact that the understanding of time differs in children compared with adults; therefore, when making decisions, only the current difficulties and short-term consequences of their behavior are considered [35]. Suicide attempt relapse was detected in one-third of our study group.…”
Section: Discussionmentioning
confidence: 78%
“…in 2016 identified previous attempts to commit suicide as a key risk factor in determining potential repeated suicide attempts [35]. A review of pediatric suicides performed in the USA in 2019 for a 25 year period analyzed child and adolescent suicides and identified that one-quarter of children who committed suicide had previously attempted to commit suicide [36].…”
mentioning
confidence: 99%
“…Almost two-thirds of suicidal adolescent attempters tried to talk to their parents about their problems and felt they were not heard. There was a significant connection between this feeling, the duration of suicidal thoughts, and a committed attempt [61].…”
Section: Mental Conditionmentioning
confidence: 98%
“…Почти две трети суицидальных подростков, пытавшихся поговорить с родителями о своих проблемах, чувствовали себя неуслышанными. Между этим чувством, длительностью суицидальных мыслей и совершённой попыткой существовала значимая связь [61].…”
Section: Mental Conditionunclassified